2014
DOI: 10.1161/circgenetics.113.000395
|View full text |Cite
|
Sign up to set email alerts
|

CKM and LILRB5 Are Associated With Serum Levels of Creatine Kinase

Abstract: This is the first genome-wide study to report on the underlying genetic determinants of CK variation in a population of statin users. We found statistically significant association for variants in the CKM and LILRB5 genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 33 publications
5
30
0
2
Order By: Relevance
“…It was suggested to play a role in clearance of creatine kinase via the mononuclear phagocytic system in the liver [78]. LILRB5 is unique among LILRBs in that it is the only LILRB that is not highly expressed by M5 AML cells and in that its expres-sion does not correlate with the overall survival of AML patients based on our analysis of TCGA database of AML patients (https://tcga-data.nci.nih.gov/tcga/).…”
Section: Lilrb5 (Cd85c Lir8)mentioning
confidence: 99%
“…It was suggested to play a role in clearance of creatine kinase via the mononuclear phagocytic system in the liver [78]. LILRB5 is unique among LILRBs in that it is the only LILRB that is not highly expressed by M5 AML cells and in that its expres-sion does not correlate with the overall survival of AML patients based on our analysis of TCGA database of AML patients (https://tcga-data.nci.nih.gov/tcga/).…”
Section: Lilrb5 (Cd85c Lir8)mentioning
confidence: 99%
“…3,10 In this issue, Siddiqui et al 11 have further investigated the contribution of CKM Glu83Gly (rs11559024) in explaining the variability in CK levels and whether or not it could help identify patients at a higher risk of statin-induced myalgia. CKM encodes for 1 of the 2 CK dimers, CK-M. 1 The study by Siddiqui et al 11 builds on previous reports from our 12 and other groups 2,13 which have found that genetic variants in the CKM gene influence CK levels. In the current study, the authors have further validated the association between the rs11559024 variant (Glu83Gly) in the CKM gene and baseline CK levels in the GoDARTS (Genetics of Diabetes Audit and Research, Tayside Scotland) and JUPITER (Justification for the Use of Statins in Prevention: An Intervention Trial Evaluating Rosuvastatin) populations.…”
Section: See Article By Siddiqui Et Almentioning
confidence: 84%
“…They also report that statin dose and duration of use did not impact this association. 23 The minor allele frequency (MAF) in the Canadian study was 0.010. 23 Kristjansson et al 4 replicated these findings in a genome-wide association study performed on 63 159 Icelanders with CK measurements.…”
Section: See Editorial By De Denus Et Al See Clinical Perspectivementioning
confidence: 95%
“…23 The minor allele frequency (MAF) in the Canadian study was 0.010. 23 Kristjansson et al 4 replicated these findings in a genome-wide association study performed on 63 159 Icelanders with CK measurements. They report the main effect of the CKM Glu83Gly variant as being associated with serum CK (β=−0.446, P value=1.8×10 −115 ).…”
Section: See Editorial By De Denus Et Al See Clinical Perspectivementioning
confidence: 95%
See 1 more Smart Citation